THE EFFECT OF CLINICAL PATHWAY TOWARD HOSPITALâS QUALITY AND COST IN âRSUSâ HOSPITAL BANDAR LAMPUNG - Himawati, Toki; Bachtiar, Adang (Proceedings of the International Conference on Applied Science and Health, 2018)
Background: One of the most appropriate policies to overcome the over budget is the quality control of cost control, the instrument is a clinical pathway, so that the hospital can perform service functions well and quality without experiencing financial loss. This research has a purpose to know how far is clinical pathway can be good as a tool of quality control of cost control at âRSUSâ Hospital Bandar Lampung. Methods: The research used a qualitative research involved 35 informants comprised of shareholders, Board of Directors, Medical Committee, Provision of Care Services and Coder. Results: The results showed that in general, the informants agreed with the implementation of the clinical pathway because it can improve the quality of service, the certainty of procedures and can overcome the budget. Conclusion: RSUS Hospital has not fully use clinical pathway as a tool of quality control of cost control, thus over budget remains with low quality of serviceÂ